A Web-Based Edulab and Problem-Based Learning Framework for Enhancing Conceptual Understanding in Cell Biology - Laili, Faizatun Nisful; Zubaidah, Siti; Setiowati, Frida Kunti; Hardianto (Jurnal Paedagogy, 2026)
This study aims to examine the effectiveness of an integrated instructional framework combining Web-Based Edulab (WBE) and Problem-Based Learning (PBL) in enhancing students’ conceptual understanding in cell biology. This study employed a quasi-experimental design using a non-equivalent control group structure. The study was conducted at a public senior high school in Malang, East Java, Indonesia. A total of 69 Grade XI students participated in the study, with 35 students assigned to the experimental group and 34 students assigned to the control group.. The experimental group received instruction through the integration of WBE and PBL, while the control group was taught using conventional methods. Data were collected through a conceptual understanding test administered as pre-test and post-test. Prior to hypothesis testing, assumption tests including normality and homogeneity were conducted. The data were then analyzed using Analysis of Covariance (ANCOVA) with pre-test scores as the covariate. The results revealed a statistically significant effect of the instructional intervention on students’ conceptual understanding (F(1,66) = 4.084, p = 0.047, ηp² = 0.058), indicating a moderate effect size. The experimental group achieved a higher adjusted mean score (M = 83.548) than the control group (M = 77.820), suggesting that the WBE–PBL framework effectively improved students’ conceptual understanding in cell biology. These findings demonstrate that integrating interactive digital learning environments with inquiry-based pedagogy can promote deeper cognitive engagement and facilitate meaningful knowledge construction. This study contributes to biology education by providing empirical evidence for the effectiveness of the WBE–PBL framework. Practically, biology teachers can integrate virtual laboratory simulations, interactive visualizations, and problem-based investigations into classroom instruction to support students’ exploration of abstract cellular concepts. Curriculum developers may also incorporate technology-enhanced inquiry activities into biology learning materials to strengthen conceptual understanding and promote 21st-century competencies.